KAJIAN EKOLOGI POPULASI RUSA SAMBAR (Cervus unicolor) DALAM PENGUSAHAAN TAMAN BURU GUNUNG MASIGIT KAREUMBI (Study on Ecology of Cervus unicolor Population in the Development of Gunung Masigit Kareumbi Hunting Park) - Elano Ratag; Yanto Santosa; Agus Priyono K (Department of Forest Resources Conservation and Ecotourism - IPB University, 2006)
Theresult of Citra Landsat TM in June 2001 showed that the coverage of land in Gunung Masigit Kareumbi Hunting Park area was changed. The area of protected are production forest have respectively decreased by 29.85% and 5.51%. Meanwhile, the result of vegetation analysis showed that there has been found 87 kinds of vegetation, consisting of 44 kinds of plantation and 43 kinds of the forage. Most (63,64%) of the forage which is food resource of rusa sambar is categorized as Poacea family. Notably, the total biomass productivity of forage is 20.790.6 kg/ha/year.The effective width of area is 6.900.1 ha, while the total of potential grassing of all sp-ecies of forage in Gunung Masigit Kareumbi Hunting Park is 47.394.028.5 kg/year. Carrying capacity of this area is 22.780 individuals. Hunting season is after 4 years of population introduced. The number of individuals introduced to fulfil hunting target is 4.280 of adult, consis of 713 males and 3.567 females.Key words : cervus unicolor, vegetation, carying capacity, hunting target, population